Effects of temperature mode and the substrate/inoculum ratio on anaerobic digestion of Tibetan food waste. Issue 3 (1st November 2021) - Song, Yingjin; Li, Yihang; Chen, Guanyi; Yan, Beibei; Li, Jinlei; Li, Hongji; Li, Ruiyi; Wang, Yuxin; Zhang, Yingxiu
Abstract: BACKGROUND: The research and applications of anaerobic digestion (AD) in plateau areas are limited by the specific climatic conditions (e.g., low temperature, large temperature difference). To explore feasible and economical strategies of AD in these regions, the effects of different temperature modes (constant mode: 35, 25, 15 °C; stepwise changes mode that simulated daily environmental temperature changes: 35–25 °C, 25–15 °C) and substrate/inoculum (S/I) ratios (1: 1, 1: 2, 1: 4) on Tibetan food waste (FW) digestion performance and microbial community structure were analyzed. Besides this, the energy balance of AD under different conditions was estimated. RESULTS: The methane yields (335–463 mL g −1 VS ) of FW at temperature changes mode with less energy consumption could reach the same level or even slightly higher than the methane yields at 35 °C. Kinetic analysis revealed that, compared with 25 °C, methane production performance was not greatly affected by temperature fluctuations around 25 °C. The relative abundance of acetoclastic methanogens (e.g., Methanosaeta ) were dominant over hydrogenotrophic methanogens (e.g., Methanobacterium, Methanospirillum ) at 35 °C. The opposite was true at 15 °C. CONCLUSION: The decrease in temperature caused the digestion pathway to shift from acetoclastic to the hydrogenotrophic pathway. The effect of temperature on the microbial community structure was more pronounced than the S/I ratio. Energy balance calculations showed that psychrophilic conditions and AD without temperature control were likely to be more economically competitive than mesophilic conditions for small‐scale AD in cold regions. © 2021 Society of Chemical Industry (SCI).